Challenges of Individualization - Genov, Nikolai (Palgrave Macmillan UK, 2018)
This book critically engages with a series of provocative questions that ask: Why are contemporary societies so dependent on constructive and destructive effects of individualization? Is this phenomenon only related to the 'second' or 'late' modernity? Can the concept of individualization be productively used for developing a sociological diagnosis of our time? The innovative answers suggested in this book are focused on two types of challenges accompanying the rise of individualization. First, that it is caused by controversial changes in social structures and action patterns. Second, that the effects of individualization question varieties of the common good. Both challenges have a long history but reached critical intensity in advanced contemporary societies in the context of current globalization.